Doses de fósforo na fertirrigação de mudas em substrato a base de fibra de coco e influência na produção do repolho - Cimó, Leon [UNESP]; Candian, Joara Secchi [UNESP]; Colombari, Lidiane Fernandes [UNESP]; Redigolo, Mateus Vinícius Narciso [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2017)
Cabbage is a species propagated by seeds, with production of seedlings in tray, however, there are few studies on fertigation with nutrient solutions in this stage of the plants’ cycle. The objective of this study was to evaluate the influence of phosphorus doses on fertigation of seedlings in cabbage production. Six doses of phosphorus (0, 15, 30, 45, 60 and 75 mg of P L-1) were evaluated in a randomized block design. Four fertigations were made at 7, 14, 21 and 28 days after sowing. The characteristics evaluated in seedling stage were: number of leaves, height, fresh and dry weight of aerial parts and roots. The characteristics evaluated after harvest were: number of external and internal (head) of leaves, mass of fresh matter of external and internal (“head”) leaves, diameter and height of the “head”. There was a linear increase in the height and dry matter weight of the roots of seedlings the higher is the phosphorus dose. For number of leaves, fresh and dry matter weight of aerial parts and dry weight of root it was obtained quadratic effect, with maximum estimated values for doses ranging from 40 to 61 mg of P L-1. However, there were no significant differences for all traits evaluated at harvest, probably because after transplantation there was good plant growth in all treatments and the initial differences did not remain until the end of the cycle.
Doses of phosphorus used in fertigation of seedlings and their influence on cabbage production
Keywords: Brassica oleracea var. capitata; Coconut’s husk fiber; Phosphate fertilizer